Emerging crosslinking techniques for glove manufacturers with improved nitrile glove properties and reduced allergic risks. (June 2019) - Yew, Guo Yong; Tham, Thing Chai; Law, Chung Lim; Chu, Dinh-Toi; Ogino, Chiaki; Show, Pau Loke
Graphical abstract: Highlights: An accelerator free crosslinker for rubber polymer. A crosslinker which could alternate the physical properties of nitrile rubber. A quality nitrile rubber with high tensile strength and elongation properties. Metal Ions exist in rubber compounding formulation with positive effect. Bonding characteristic of nitrile rubber. Abstract: The long revolution of nitrile rubber in the rubber industries, especially for lightly crosslinked products has been reviewed in this paper. The advancement is remarkable from the first invention of acrylonitrile butadiene rubber and till date, the physical and chemical properties were elevated. Recent rubber chemists are mainly focus in modifying the nature of the synthetic latex based on butadiene and crosslinker to enhance the performability for rubber product to be used in broad range of applications. Besides, the different types of rubber had contribute to different sectors of usage due to their speciality properties. All belong to the effort of various types of crosslinking methods which making the liquid latex to suit in plenty of applications and usage from space shuttle (O-ring) to food hawker hygiene gloves. This paper summarized all sort of gloves products in comparison with nitrile rubber glove. Natural rubber is a superior latex glove which show high elasticity and tactility however not suitable for medical usage due to its protein allergic issues. Moreover, current development of natural rubber by synthesis through, in vitro and in vivo method, with the aim to produce equivalent properties of rubber product with lower materials cost. In fact, the glove manufacturing process have various parameters to monitor to produce a accepted quality of gloves. A quality of nitrile glove may need to pay close attention on latex compounding formulation and choice of the value-added process options. Metal ions crosslinker shows an exceptional cost and time saving for crosslinking especially on nitrile rubber. The discussion on the bonding characteristic which contribute for the tensile strength and durability of the nitrile rubber glove.